Desarrollo de un algoritmo matemático de optimización convexa para el cálculo de pérdidas en las redes eléctricas de distribución. - Naula Naula, Michael Froilan (2020)
The present investigation raises on the development of a mathematical algorithm of convex opti- mization, at this investigation is introduced essential techniques to give solutions to power flow problems (OPF), where these techniques can be linear programming, conical programming, second conical programming order and semi-defined programming (SDP). The semi-defined programming technique is used that approximates to the traditional equations of power flow reaching optimal approximations that provide a global optimum. The mathematical method is compared with the formulation (non-linear / non-convex) of the optimal power flow using dif- ferent traditional solvers. In order to solve the power flow in radial networks, mathematical optimization strategies need to be used in this way by linearizing the problem, the semi-defined programming method (SDP) proposes a mathematical formulation that solves non-linear pro- blems through convex approximations of easy solution. Obtained results from the proposed method are identical to the optimal non-linear power flow complying with definition of strong duality.